Electrophoretic analysis of proteins from raw materials and commercial diets used in animal feed - Isea-León, Fernando; Saltos, Luis David Balarezo; Parra, Jean Carlos Pérez; Obando, María Belén Vinces; A. L, Medina; Delgado, Juan Manuel Vera; Useche, Lelly; Piedra, Felipe Jadán (Edelweiss Applied Science and Technology, 2024)
In aquaculture, balanced feed accounts for 50% to 70% of the operational costs of cultivating aquatic organisms. This feed is made from various raw materials that serve as protein sources, which significantly influence the final cost of the feed. Therefore, an electrophoretic study was conducted to compare the protein content in different raw materials and commercial diets used in animal feed. Electrophoretic profiles with standard concentration gels (SDS-PAGE) were used to separate protein fractions from animal-origin raw materials, including Earthworm Meals of Eisenia andrei (HLF) and Eisenia fetida (HLT), meat-bone meal (MBM), and fish meal (FM), as well as plant-origin meals, such as Leucaena leaf meal (LLM), corn meal (YCM), and wheat bran (WBM). Commercial diets (A, B, and C) were also evaluated. The protein content of the samples was determined. For electrophoretic analysis, a protease inhibitor cocktail was used, along with a molecular weight standard with a range from 250 to 4 kDa. The molecular weights of the diets ranged between 31.1 and 234.1 kDa, 36.3 and 190.4 kDa, and 4.281 and 95.685 kDa. Some of the protein bands in the analyzed samples (HLF, HLT, FM, YCM, and WBM) were very close to the reference protein bands at 148, 98, 64, 50, and 36 kDa, corresponding to the molecular weight standard used. Electrophoretic characterization provided insight into the different protein fractions, offering valuable information about their potential functional and nutritional properties. Electrophoresis is an essential analytical tool for assessing both the quality and safety of raw materials and foods.